Para além das condicionalidades : desafios para o programa bolsa família no município de Esteio/RS - Teixeira, Renato de Oliveira (2014)
This dissertation has as its theme the Bolsa Família´s Program (BFP) in the municipality of Esteio/RS, and the relationship between public policies of social welfare, education and health derived from conditionalities and the challenges towards the construction of intersectionality. It is proposed to systematize the results of a research conducted in 2013, which had the overall objective of verifying whether the conditionalities of BFP potentiate the intersectionality between public policies of social welfare, education and health from the experiences brought by beneficiary families and by workers and managers involved the actions of the program in the municipality of Esteio/RS. With a critical dialectic perspective, this qualitative study, with contributions of quantitative data provides references related to this topic, the historical background of the PBF and its relationship with the social question, the prospect of targeting, conditionalities and intersectionality. Had as research subjects: four women's legal guardian of the beneficiary families of BFP, three workers and three managers of policies involved the PBF. Among the key findings are the sociodemographic characteristics of families benefiting from the program based on the systematization of the analysis of quantitative data from CADÚNICO and PBF. In their qualitative part, we used the content analysis technique, which allowed the emergence of perceptions, experiences and opinions of the three segments addressed. Among the families and their relationship with the program, the data indicates the bureaucracy in access , the waiting time for the benefit, the demand for oversight of the program, and the conditionalities as an affirming element of the division of labor based on gender , their perceptions of conditionalities of the program, crossed by precariousness as a manifestation of structural violence, among the segment of workers, the concern with dependence on money, generating autonomy and emancipation in the program, a look of accountability arises from families as responsible for their conditions of poverty , the yearning for further actions and the need to define the services provided. Also the experience of the precariousness of the lack of human resources and infrastructure. On the positive side, there is the bond with the families and the possibility of prevention of diseases related to nutritional status. Between managers: understand that the PBF contributes in income generation and responsibility of families. Compliance with the counterparts, one finds the concept of BFP as a program in motion and perceive advances, as on the school frequency. Regarding health, there is the understanding that greater accountability of family health teams for family support and intensification of actions is required. On the positive side, emerges the idea that the BFP seeks a transformative perspective and overcome welfarism. Such analysis of these results indicate the need for further development and qualification of the relationship between public policies related to BFP , in the context of managing and implementing the program as well as related to the families benefiting from the program.